2021
DOI: 10.1021/acs.orglett.1c02659
|View full text |Cite
|
Sign up to set email alerts
|

HFIP-Catalyzed Difluoroalkylation of Propargylic Alcohols to Access Tetrasubstituted Difluoroalkyl Allenes

Abstract: A hexafluoroisopropanol (HFIP)-catalyzed difluoroalkylation of propargylic alcohols with difluoroenoxysilanes to access structurally diverse tetrasubstituted difluoroalkyl allenes has been developed. This convenient procedure enables the rapid construction of highly functionalized multisubstituted fluorinated allenes in a mild and straightforward way. Furthermore, the synthetic potential of this methodology has been demonstrated by the facile synthesis of various structurally interesting fluorinecontaining mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 63 publications
1
13
0
1
Order By: Relevance
“…Thus, developing more efficient synthetic methods or catalytic systems of such compounds is still one of the fascinating problems to be solved. In view of the excellent performance of fluoroalcohol catalysis in the construction of fluorinated compounds in our recent studies, there is reason to believe that the fluoroalcohol-catalyzed strategy has the potential to solve the Mukaiyama aldol reaction of ketoaldehydes with difluoroenoxysilanes efficiently by virtue of multiple hydrogen bond interactions . Herein, we describe our efforts to develop the HFIP-catalyzed Mukaiyama aldol reaction of readily available glyoxal monohydrates with difluoroenoxysilanes to access structurally diverse 2,2-difluoro-3-hydroxy-1,4-diketones under mild reaction conditions (Scheme B).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, developing more efficient synthetic methods or catalytic systems of such compounds is still one of the fascinating problems to be solved. In view of the excellent performance of fluoroalcohol catalysis in the construction of fluorinated compounds in our recent studies, there is reason to believe that the fluoroalcohol-catalyzed strategy has the potential to solve the Mukaiyama aldol reaction of ketoaldehydes with difluoroenoxysilanes efficiently by virtue of multiple hydrogen bond interactions . Herein, we describe our efforts to develop the HFIP-catalyzed Mukaiyama aldol reaction of readily available glyoxal monohydrates with difluoroenoxysilanes to access structurally diverse 2,2-difluoro-3-hydroxy-1,4-diketones under mild reaction conditions (Scheme B).…”
Section: Introductionmentioning
confidence: 99%
“…Though difluoroenoxysilanes have been recognized as versatile synthons for constructing diverse difluoroalkylated molecules in the past decade due to their facile preparation and good stability, the catalytic asymmetric synthesis with difluoroenoxysilanes is still in its infancy . Quite a number of reactions were conducted in a racemic manner, though numerous attempts have been made on asymmetric reactions. , For instance, the Mukaiyama–Mannich reaction of difluoroenoxysilanes 2 with N -Boc isatin ketimines 1 developed by Zhou and co-workers in 2015 provided racemic products 3 efficiently. Albeit a wide screening of chiral catalysts, the results remain unsatisfactory (Scheme ).…”
mentioning
confidence: 99%
“…Especially, 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP) has been applied to activate carbonyl compounds, alkenes, epoxides, benzyl halides, nitrostyrenes, and alcohols in F–C reaction sequence, probably due to its high H-bond donating ability, mild acidity, and strong cation stabilization. In our recent studies, it was found HFIP could be used as a novel and efficient catalyst for the C–C bond formation through the C–O bond cleavages of π-activate alcohols with difluoroenoxysilanes . Given the prominent catalytic activities of HFIP with OH-containing compounds, we speculated that the H-bond networks of HFIP could activate arylglyoxal hydrates and selectively achieve hydroxyalkylation products of anilines by adjusting the amount of HFIP in the reaction system.…”
mentioning
confidence: 99%